Clinical profile and surgical management of diabetic foot in Benghazi, Libya. Issue 1 (March 2016) - Benkhadoura, Mohamed; Alswehly, Mohamed; Elbarsha, Abdulwahab
Highlights: Medical records of 542 patients admitted with diabetic foot to a major teaching hospital were studied. 52% of patients presented with grade III–V ulcers according to Wagner's grading system. The overall amputation rate was 34%. The mortality rate was 2%, and comprised mainly patients presented as Wagner's grades IV and V and those who had comorbid diseases. There is a need to establish a dedicated facility with multidisciplinary team to improve patients outcome. Abstract: Background: The aim of this study was to outline the patterns and management of diabetic foot ulcer (DFU) and compare our experience with other published data. Patients and methods: All consecutive patients admitted to Al-Jala Hospital with diabetic foot from June, 2008 to May, 2013 were reviewed retrospectively. Results: A total of 542 patients were studied, Wagner's grade III ulcers were the most prevalent (31%), followed by grade II (25%). About 10% of patients underwent major amputations and 24.2% underwent minor amputations. The amputation rate was 34%, and the mortality rate was 2%. Conclusion: Diabetic foot infections cause significant morbidity and mortality among patients with diabetes in Benghazi. There is a need to establish a diabetic foot clinic in Benghazi with a multidisciplinary team to reduce the rates of hospital admission and amputation, as well as hospital stay duration.